Analysis of the impacts and risks of quantitative easing conducted by the Federal Reserve System between 2008 and 2020 - Votava, Michal (2022)
This thesis uses regression analysis to examine and quantify the effects of quantitative easing on the U.S. economy, specifically on real GDP growth, unemployment, inflation, and U.S. Treasury yields. It also examines the impact on the domestic currencies of selected foreign economies. The theoretical section briefly discusses the history, transmission mechanism and benefits and risks associated with quantitative easing. The practical part then uses regression models, where quantitative easing is represented by mortgage-backed securities, and US Treasury bonds held on the Fed's balance sheet, to establish the correlation between the variables tested, thus confirming the relationship between quantitative easing and real GDP growth and inflation, as well as the decline in unemployment and US Treasury bond yields. The results also show that the effects of quantitative easing spill over to foreign economies, where they have a positive effect on the exchange rate of the local currency, which, among other things, threatens the competitiveness of the domestic economy.